Assessment of COVID-19 outbreaks in long-term care facilities. (April 2023) - Bennett, C.C.; Welton, M.; Bos, J.; Moon, G.; Berkley, A.; Kavlak, L.; Pearson, J.; Turabelidze, G.; Frazier, J.; Fehrenbach, N.; Brown, C.K.
Summary: Background: The B.1.167.2 (Delta) variant quickly became the predominant circulating SARS-CoV-2 strain in the USA during summer 2021. Missouri identified a high number of outbreaks in long-term care facilities (LTCFs) across the state with low vaccination rates among LTCF staff members and poor adherence to mitigation measures within local communities. Aim: To describe COVID-19 outbreaks that occurred in Missouri LTCFs impacting staff and residents during the surge of the Delta variant. Methods: Outbreaks of COVID-19 in 178 LTCFs were identified by the Missouri Department of Health and Senior Services. Case data from LTCFs with the highest burden of disease were analysed to assess disease transmission, vaccination status, and outcomes among residents and staff. Additional investigational measures included onsite visits to facilities with recent COVID-19 outbreaks in communities with substantial transmission to assess mitigation measures. Findings: During April 22 nd to July 29 th, 2021, 159 COVID-19 cases among 72 staff members and 87 residents were identified in 10 LTCFs. More than 74.7% of resident cases were vaccinated compared to 23.6% of staff cases. Vaccinated residents had a lower proportion of hospitalizations and deaths reported compared to unvaccinated residents. Data analysis and contact-tracing efforts from a sample of the facilities suggest that staff members were likely a major factor in introducing SARS-CoV-2 virus into the facilities. Adherence to COVID-19 mitigation measures varied at the visited facilities. Conclusion: Data showed that vaccination rates varied between staff cases and resident cases in facilities with high-burden outbreaks. Differences were identified in mitigation practices in at least two facilities.